Bioinorganic chemistry of synucleinopathies: Deciphering the binding features of Met motifs and His-50 in AS-Cu(I) interactions - Miotto, Marco César (2014)
The aggregation of alpha-synuclein (AS) is a critical step in the etiology of Parkinson's disease (PD) and other neurodegenerative synucleinopathies. This process is selectively enhanced by copper in vitro and the interaction is proposed to play a potential role in vivo. Presently, the identity of the Cu(I) binding sites in AS and their relative affinities are under debate. In this work we have addressed unresolved details related to the structural binding specificity and affinity of Cu(I) to full-length AS. We demonstrated conclusively that: (i) the binding preferences of Cu(I) for the Met-binding sites at the N- (Kd = 20 μM) and C-terminus (Kd = 270 μM) of AS are widely different: (ii) the imidazole ring of His-50 acts as an effective anchoring residue (Kd = 50 μM) for Cu(I) binding to AS; and (iii) no major structural rearrangements occur in the protein upon Cu(I) binding. Overall, our work shows that Cu(I) binding to the N- and C-terminal regions of AS are two independent events, with substantial differences in their affinities, and suggest that protein oxidative damage derived from a misbalance in cellular copper homeostasis would target preferentially the N-terminal region of AS. This knowledge is key to understanding the structural-aggregation basis of the copper catalyzed oxidation of AS.